Longitudinally Extensive Transverse Myelitis as Presenting Manifestation of Lung Adenocarcinoma - Rana, Davinder Singh; Rohatgi, Anshu; Patel, Samir; Dave, Nikhil; Agarwal, Rajat; Gupta, Pooja (Indian Journal of Medical and Paediatric Oncology, 2018)
Longitudinally extensive transverse myelitis (LETM) is an unusual manifestation of systemic malignancy. It has been mainly reported with lung cancers and lymphoproliferative malignancy. LETM in systemic malignancy can be caused by either intramedullary metastases or paraneoplastic syndrome. Occurrence of LETM as the first manifestation of malignancy has been rarely reported. We present clinical, laboratory, and imaging findings of a 66-year-old man with nonsmall-cell lung (adeno) carcinoma, who presented with LETM without having any cardinal manifestations of lung malignancy. The rarity of the disease and especially such a presentation can cause considerable delay in the diagnosis and treatment.
Keywords: Longitudinally extensive transverse myelitis; lung adenocarcinoma; systemic malignancy